La formación del profesorado universitario como acción estratégica en la mejora de la calidad institucional - Garcia Del Dujo, Angel (Revista Española de Pedagogía, 2018)
This article shows how the university teachers training must be seen as strategic action to improve the institutional quality. An utilitarian and mass university, as we think the university in our days is, requires inmediate attention about the way the internal elements of the system are affected. One of these elements, perhaps the most sensitive at the point of strategic view, is the university teachers. In this work we analyze the disconcerting and problematic situation they have in the research and teaching activities and we propose the pedagogical and vocational training as the best way to improve the institutional quality
Keywords: formación; profesorado universitario; acción estratégica; calidad institucional; Revista Española de Pedagogía